Cabergoline may act as a radioprotective agent in Cushing's disease. (22nd November 2019) - Thakkar, Kunal; Lila, Anurag; Sarathi, Vijaya; Ramteke‐Jadhav, Swati; Goroshi, Manjunath; Memon, Saba Samad; Krishnatry, Rahul; Gupta, Tejpal; Jalali, Rakesh; Goel, Atul; Shah, Abhidha; Sankhe, Shilpa; et al.
Abstract: Context: Conventional fractionated radiotherapy (CRT) achieves control of pathological hypercortisolism in 75%‐80% of patients with persistent or recurrent Cushing's disease (CD), over a mean period of 18‐24 months. Medical therapy is recommended as bridge therapy while awaiting RT effect. Objective: To determine long‐term outcome of CRT and its predictors in CD patients. Design, Setting and Patients: This is a retrospective case record analysis of 42 patients with CD who received CRT as a treatment modality and had at least 12 months post‐RT follow‐up. The dose delivered was 45 Gy in 25 fractions over 5 weeks. Demographic details, hormonal evaluation and radiological data were extracted from case records. Dexamethasone suppressed cortisol at cut‐off of 1.8 µg/dL was used to define remission or recurrence. Possible predictors for remission and recurrence were analysed. Results: The mean age at the time of CRT administration was 23.7 ± 10.7 (range: 12‐48) years. A total of 29 (69%) patients achieved remission 26.5 ± 28.5 (median: 18, range: 3‐120) months after RT, while 13 (31%) patients had persistent disease at last follow‐up. There were no significant predictors of disease remission after CRT. Six (20.7%) patients had recurrence after a documented initial remission. Recurrence occurred 66.6 ± 25.9 (median: 74; range: 18 to 90) months after documented remission. Recurrence of the disease was exclusively seen in patients who received peri‐RT cabergoline. Peri‐CRT use of cabergoline was significantly associated with increased recurrence rates ( P  = .016). Conclusion: Use of cabergoline in the peri‐CRT period did not affect initial remission after CRT but was associated with increased recurrence after initial remission in CD.